The Participation of Rural Afghan Women in Small-Scale Dairy Farming - Khail, Miraqa Hussain; Ahmadzai, Khal Mohammad (International Journal of Innovative Research and Scientific Studies, 2022)
Afghanistan is an agricultural country, where more than 80% of the population depends on agriculture for their livelihoods. The livestock sector contributes perhaps half of the licit agriculture’s contribution to the national GDP. Small-scale dairy farming is an important component of Afghanistan’s rural economy. Milk and dairy products are crucial for the daily food security and income generation of most Afghan households. Rural women play a significant role in agriculture production, but their contribution remains un-recognized by researchers and policymakers. This study intends to examine the role and extent of the participation of rural women in small-scale dairy farming. There are no data available for an objective understanding of the role played by women in the rural economy of Afghanistan. The data was obtained from a sample of 180 rural women using a random sampling technique through a dairy farm survey in the Mousahi district of Kabul, Afghanistan during August and September 2021. Descriptive statistical tools like frequency, average, and percentage were used for the analysis. The study concluded that rural women’s contribution is one of the most significant elements of the operation of small-scale dairy farming, and most dairy farming work, from fodder collection to feeding, watering, animal management, and health care, is conducted by women.